Biraderi, Bloc Votes and Bradford: Investigating the Respect Party's Campaign Strategy. (15th July 2014) - Peace, Timothy; Akhtar, Parveen
Research Highlights and Abstract This article Contributes to theoretical debates on minority political participation in the UK, with specific reference to inter‐generational variations within the South Asian Muslim community; Contributes to the scholarly literature on the impact and effectiveness of new political parties within the British political system, through a case study of the Respect Party; Adds to empirical primary data on strategies adopted by political parties in courting specific sections of the ethnic minority vote in the UK; Offers an empirically‐led demonstration of the changes taking place within the political sphere of South Asian Muslim diasporas in Britain. In March 2012, the Respect Party won an unexpected by‐election in the British city of Bradford, previously regarded as a safe Labour seat. This article examines the party's campaign strategy and in particular how it courted South Asian Muslim voters. A dominant feature of South Asian Muslim politics in the UK has been community bloc voting along lines of kinship (biraderi). The use of kinship networks for political gain effectively disenfranchised many young people and women. We demonstrate how Respect used their experience of campaigning in constituencies with significant numbers of South Asian Muslim voters to achieve an unlikely victory in Bradford. A key strategy was to mobilise otherwise politically marginalised sections of the South Asian Muslim community by offering an alternative to the culture of patronage in Bradford whilst at the same time utilising certain community structures in order to gain their own bloc votes.